Pembelajaran tentang Tugas dan Wewenang Bagi Penjaga Perlintasan Sebidang dengan Jalan Raya - Dhina Setyo Oktaria; Arief Darmawan; Balla Wahyu Budiarto; Handoko Handoko (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Learning is a knowledge transfer process involving the system in the education world: teachers/educators, students, materials, goals, and tools. The purpose of this education and training is to transfer and share knowledge and experience between instructors and training participants regarding the duties and authorities of crossing guards on a railroad plot with a highway. The method used is face-to-face learning with 2 JP or 100 minutes. The teacher gives a questionnaire that the training participants fill out. The questionnaire contains the latest education, work area, and 13 (thirteen) questions related to the duties and authorities of a level crossing guard with a highway. The results of the questionnaire obtained that there were still 6 participants whose total percentage of answers was still below 60%, and there were still 14 participants whose percentage of responses was still below 70%. There are 5 participants whose answer percentage is 100%. Based on this, learning is still needed to increase the knowledge and competence of each individual because safety at level crossings is an absolute thing. After all, it is related to the safety of lives and objects of road users who pass at level crossings.